Preventivni vadbeni program PEP za zmanjševanje poškodb kolena pri športnicah - Palma, Polona (Šport (Ljubljana), 2020)
Introduction: Neuro-muscular prevention programs are designed to improve the joint position sense, increase joint stability, and develop protective mechanisms to reduce the chance of lower limb injury. One of these programe is called "Prevention injury, enhance performance - PEP". Purpose: To analyse effects of PEP program on the prevention of knee injuries in female football and basketball players. Methods: A literature review was conducted in databases PubMed, Cochrane library, Dikul and Pedro. Keywords in English were used in different combinations. Results: Eight studies were included. In two of them reduced incidence of knee injuries or anterior cruciate ligaments injuries, in three studies improved different parameters of landing and in two studies improved muscle balance between the hamstring and the quadriceps muscle, were determined. None of the three studies founded improvement in vertical jump height. Conclusions: The PEP program is effective in reducing knee injuries, improving knee biomechanics at landing, and muscular balance between knee flexors and extensors muscles. However, it has no influence on improving the performance of sports activities.
Keywords: anterior cruciate ligament; female athletes; knee injury; neuro-muscular prevention program; PEP program; program PEP; sport; sprednja križna vez; šport; športne poškodbe; športnice; živčno-mišični preventivni program